Using AI calving-ease bulls on replacement heifers - K.A. Heikes (Kansas Agricultural Experiment Station Research Reports, 1986)
For maximal genetic progress in a dairy, proven AI sires should be selected to use on replacement heifers. To minimize problems at calving, these sires should be selected from bulls that are breed average or better for calving ease.; Dairy Day, 1986, Kansas State University, Manhattan, KS, 1986;
Keywords: Kansas Agricultural Experiment Station contribution; no. 87-88-S; Report of progress (Kansas Agricultural Experiment Station); 506; Dairy; Artificial Insemination (AI); Calving-ease; Replacement heifers